Corporal punishment: the case of a child abuse by a Malaysian couple in Sweden - Islam, Md. Zahidul; Rahman, Md.Mashiur (American-Eurasian Network for Scientific Information Publications(AENSI), 2018)
Corporal punishment is a form of physical punishment which is a common and debatable issue. International laws as well as the laws of many countries have prohibited corporal punishment. The aim of this paper is to focus on the present position of Malaysia and Sweden regarding corporal punishment. It is a qualitative research. The information has been taken from many readings, articles, books, newspapers and statutes. A Malaysian couple has been arrested by Swedish police for hitting their children for not performing prayer. As a Muslim country, Malaysia is practicing corporal punishment from the beginning. Islam allows corporal punishment to children for teaching discipline as well as correction. On the other hand, it is strictly prohibited in Sweden.